CEFALEIA NA GESTAÇÃO E PUERPÉRIO: DESENVOLVIMENTO DE VÍDEOAULA COMO TECNOLOGIA DE INFORMAÇÃO E COMUNICAÇÃO - Teixeira, Daniela Oliveira (2019)
Introduction: During pregnancy, there may be several abnormal symptoms, among which stands out the headache, which even seeming common, can not be trivialized, being essential that health professionals are aware of the signs and symptoms manifested by the pregnant woman. appear sporadically even in pregnancy considered as usual risk. Objectives: To know the association of headache characteristics in pregnant women with normal risk with gestational and immediate postpartum variables that may influence the satisfaction of Basic Human Needs during pregnancy. Describe the events that worsen or ameliorate the headache, as well as the signs and symptoms that manifest before and during the headache. Elaborate a video lesson, addressing the etiology, pathophysiology and complications of headache, as well as its complications during the gestational period. Methodology: Cross-sectional quantitative study nested in a cohort research, being a clipping of a larger research entitled “Aspects related to the development and growth of infants: a birth cohort”. The sample was for convenience and consisted of 177 postpartum mothers admitted to the maternity ward of a Public Hospital in the Central Region of Rio Grande do Sul-RS. It occurred from August 2018 to April 2019. Data were collected from the health record, the pregnant woman's card and a questionnaire conducted with mothers who were admitted to this maternity hospital within 48 hours after delivery. Results: From the total of 177 postpartum women, they had a mean age of 23.21 ± 0.07 years. The average prenatal visit was 5.06 ± 2.17, and only 4 (2.2%) did not have prenatal care. The average gestational age was 39.50 ± 1.38 weeks. There is no significant association between the presence of headache in pregnant and postpartum women with socioeconomic factors, but among the 91 mothers who reported headache at one time during pregnancy, 43 (46.2) were from socioeconomic class C, 55 (60.4%). ) were married, 63 (71.6%) were white and 40 (44%) completed elementary school. Among the 6 who presented postpartum headache 4 (66.7%) were from socioeconomic class C, 5 (83.3%) were single. There was no association between headache and variables related to the immediate postpartum period, but there was a higher prevalence of headache among mothers who had cesarean section, that the babies were exclusively breastfed and those who felt insecure. Product and its applicability: Contemporary technology has emphasized a new teaching-learning model enabling numerous ways to grasp and enticing practitioners to be teachable. A didactic instrument of the video class type, considered digital tool was developed. This video discusses the different types of headache, main causes and appropriate conduct with pregnant and postpartum women. This didactic audiovisual technology adds more knowledge among the receivers and protagonists. And its applicability is easily accessible and is freely available to students, health professionals and other public interested in the subject. Final considerations: It was evidenced headache in pregnancy and postpartum, in a higher proportion in single women, being related to stress and absence of a companion that provides them with security. The eyes of professionals should pay attention to the improvement of management, offering better behavior to pregnant women. The video class can anchor and clarify these behaviors regarding care with the presence of headache during pregnancy and postpartum, clarifying doubts for professionals. For this, it is important that health professionals know how to differentiate the types of headache manifested by mothers who have recently given birth.